Unions Power, Collective Bargaining and Optimal Monetary Policy - Ester Faia; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2010)
We study Ramsey policies and optimal monetary policy rules in a model with sticky prices and unionized labour markets. Collective wage bargaining and unions monopoly power dampen wage fluctuations and amplify employment fluctuations relatively to a DNK model. The optimal monetary policy must trade-off between stabilizing inflation and reducing inefficient unemployment fluctuations induced by unions' monopoly power. In this context the monetary authority uses inflation as a tax on unions' rents. The optimal monetary policy rule targets unemployment alongside inflation.
Keywords: 330